PENGUATAN PERAN IBU MENYUSUI DALAM UPAYA PENINGKATAN PRODUKSI ASI DENGAN MENGGUNAKAN TEKNIK HYPNOBREASTFEEDING - Fitriasnani, Meirna Eka; Prasetyanti, Dhita Kris; Rif’atul Himmah, Fithri; Nikmatul Nikmah, Anis; Mega Puspita, Nara Lintan; Kusuma Dewi, Rahma; Putri Ardela, Mayasari; Aminah, Siti (Jurnal Abdi Masyarakat, 2024)
Mother's milk (ASI) contains high nutrients which are very beneficial for the baby's health. Mother's milk is the only perfect and best food for babies because it contains the nutritional elements needed by babies for the baby's growth and development in order to achieve optimal baby growth and development. Knowledge and experience regarding good and correct breastfeeding will support successful lactation. Positive attitudes that can support successful lactation include mothers immediately breastfeeding their babies within 30-50 minutes of giving birth, not wasting colostrum and using it well, breastfeeding exclusively and getting enough rest. The aim of this community service is to provide health education to breastfeeding mothers about efforts to increase breast milk production through Hypnobreastfeeding techniques. The activity participants in this service were breastfeeding mothers and cadres totaling 21 people. From the results of this community service, it is known that there is an increase in the knowledge and skills of breastfeeding mothers regarding efforts to increase breast milk production through the Hypnobreastfeeding technique. The media used in this service is booklets. It is hoped that good understanding and skills regarding efforts to increase breast milk production can increase the coverage of exclusive breastfeeding.